Magnitude, Distribution and Contextual Risk Enhancing Predictors of High 10-Year Cardiovascular Risk Among Diabetic Patients in Tanzania - Kassam, Nadeem; Surani, Salim; Hameed, Kamran; Aghan, Eric; Mayenga, Robert; Matei, Iris; Jengo, Gijsberta; Bakshi, Fatma; Mbithe, Hanifa; Orwa, James; Udeani, George; Somji, Samina (Patient related outcome measures, 2023)
Atherosclerotic Cardiovascular Disease (ASCVD) is the leading cause of death worldwide. In Diabetics, ASCVD is associated with poor prognosis and a higher case fatality rate compared with the general population. Sub-Saharan Africa is facing an epidemiological transition with ASCVD being prevalent among young adults. To date, over 20 million people have been living with DM in Africa, Tanzania being one of the five countries in the continent reported to have a higher prevalence. This study aimed to identify an individual's 10-year ASCVD absolute risk among a diabetic cohort in Tanzania and define contextual risk enhancing factors. A prospective observational study was conducted at the Aga Khan hospital, Mwanza, for a period of 8 months. The hospital is a 42-bed district-level hospital in Tanzania. Individuals 10-year risk was calculated based on the ASCVD 2013 risk calculator by ACC/AHA. Pearson's chi-square or Fischer's exact test was used to compare categorical and continuous variables. Multivariable analysis was applied to determine contextual factors for those who had a high 10-year risk of developing ASCVD. The overall cohort included 573 patients. Majority of the individuals were found to be hypertensive (n = 371, 64.7%) and obese (n = 331, 58%) having a high 10-year absolute risk (n = 343, 60%) of suffering ASCVD. The study identified duration of Diabetes Mellitus (>10 years) (OR 8.15, 95% CI 5.25-14.42), concomitant hypertension (OR 1.82 95% CI 1.06-3.06), Diabetic Dyslipidemia (OR 1.44, 95% CI 1.08-1.92) and deranged serum creatinine (OR 1.03, 95% CI 1.02-1.03) to be the risk enhancing factors amongst our population. The study confirms the majority of diabetic individuals in the lake region of Tanzania to have a high 10-year ASCVD risk. The high prevalence of obesity, hypertension and dyslipidemia augments ASCVD risk but provides interventional targets for health-care workers to decrease these alarming projections.